Mig the pig - Hawkins, Colin; Hawkins, Jacqui (New York Putnam, 1984)
Mig the Pig meets with adventure while wearing a wig and riding in a gig. Turning the narrower pages in the center of the book changes the first letter of the rhyming words.
Keywords: Children's stories, English; Toy and movable books -- Specimens; Pigs -- Fiction; Stories in rhyme; Toy and movable books